Hubungan Antara Pengetahuan Remaja Tentang Seks Dengan Pergaulan Remaja Di SMKN (Sekolah Menengah Kejuruan Negeri) Bandar Kabupaten Pacitan - Eliya Rohmah; Noka Puspitasari (Jurnal Delima Harapan, 2017)
Adolescence is a period of transition from children to adults, not just in terms ofpsychological but also physical. Even the physical changes that occur that are a primarysymptom in the juvenile growth, whereas psychological changes arise, among others, asa result of physical changes. After the interview on 5 student at SMK (Vocational HighSchool) Bandar obtained two students have good knowledge about sex and 3 studentshave knowledge about sex is lacking. Of the 123 students in grade 11, there are eightstudents out.The general objective of this research was to determine the Relationship BetweenKnowledge About Teen Sex With Teen Intercourse at SMK (Vocational High School)Bandar Pacitan. This tyipe research is analytic with cross sectional approach. A totalpopulation of 123 students. In this study used a sample of 94 students. Independentvariable in this study is the knowledge of adolescent about sex. The dependent variable isthe teenage promiscuity. In the collection of data in this study using a questionnaire.Hypothesis testing is done with the Spearman Rank correlation test.Based on the research that almost half of adolescents knowledgeable Both are 34respondents (36%), and nearly half of them (46%) have positive Teen Intercourse . Fromthe test results obtained Spearman Rank probability value (ρ) = 0,000 with significancelevel of 0.01. So there is the Relationship Between Knowledge About Teen Sex With TeenIntercourse At SMK Bandar Pacitan. With a correlation coefficient of 0.651, which showsthat the relationship strong.Expected more teachers often provide knowledge about sex, counseling andparents should supervise their children in order to control not one to hang out. And forhealth workers is expected to do counseling in schools about the knowledge of sex thatteens do not get the wrong information about sex.